The Historiography of the English State during ‘the Long Eighteenth Century’: Part I – Decentralized Perspectives - Devereaux, Simon (History compass, 2009)
This article reviews the four most prominent themes in the historiography of the modern English state during the last six decades, with a particular focus on ‘the long eighteenth century’ (1660-1837). The first is the vision of an expansive and centralized administrative state in Victorian England most famously set forth in the work of the late Oliver MacDonagh. Second is the notion of the state as an information-gathering entity that has recently been forcefully stated by Edward Higgs. Third is the vision of an unexpectedly powerful, substantially centralized ‘fiscal-military’ state during the eighteenth century, powerfully evoked in the work of John Brewer. Finally, a brief overview is given of the prodigious historical literature that has arisen in recent years surrounding the notion of the state as abstract entity capable of commanding the loyalties of those people over whom it rules. The article concludes by suggesting how a more fully integrated vision of the English state in history might be achieved through a deeper, more dynamic interrelation of changing political-administrative structures and shifting social-cultural forces.